High PV value polytetrafluoroethylene integral sliding bearing and preparation method thereof
By introducing creep-resistant polytetrafluoroethylene and fibers, combined with the modification technology of thermally conductive fillers, the problem of polytetrafluoroethylene bearings need to be combined with metal is solved, its bearing capacity and thermal conductivity are improved, and high PV value and low Friction coefficient, suitable for mechanical devices in various industries.
Patent Information
- Application Number
- CN202411624387.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-10
AI Technical Summary
Existing polytetrafluoroethylene bearings need to be compounded with metal parts and are difficult to use independently. In addition, the inorganic filler content in the composite modification technology is high, brittle, and unsatisfactory thermal conductivity, which affects its service life and reliability.
Introduce creep resistance, high-strength soluble polytetrafluoroethylene and polytetrafluoroethylene fibers, and enhance the modification of homologous polymers, combine thermal fillers to form a thermal network to improve load-bearing capacity, friction and wear performance and creep resistance. The content of inorganic lubricating filler is controlled to be less than 3%, and a low-temperature blending process is used to avoid aggregation and agglomeration.
Developed a high PV value polytetrafluoroethylene integral bearing with high load bearing, heat conductivity, strength, flexibility and excellent friction and wear performance. It is suitable for transmission parts in chemical, automobile and other industries, extending service life and improving reliability.
Smart Images

Figure CN119286171A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lubricating materials and plastic bearings, and relates to a lubricating bearing with a high PV value, in particular to a polytetrafluoroethylene sliding bearing and a preparation method thereof. Background Art
[0002] Plastic bearings have many advantages over metal sliding bearings in terms of lightweight, corrosion resistance, foreign body compatibility, vibration and noise reduction, and low cost. Therefore, their application scenarios are constantly expanding and their output is also increasing. At present, the most widely used plastic bearing substrates include polyoxymethylene, polyamide, polyetheretherketone, and polyimide. After composite modification, their mechanical strength, wear resistance, and operating temperature range are further improved, and they have been widely used. Among many polymer materials, polytetrafluoroethylene has certain advantages in self-lubricity and high temperature resistance, especially corrosion resistance, and is difficult to be replaced by other polymers; however, due to its low mechanical strength, poor load-bearing capacity, and creep resistance, its application in the bearing field is greatly limited. Existing solutions often require bonding or inlaying with metal parts for compounding, which increases the process and manufacturing costs on the one hand, and weakens the unique advantages of plastic bearings such as lightweight, corrosion resistance, and foreign body compatibility on the other hand.
[0003] After more than 60 years of development, the composite modification technology of polytetrafluoroethylene has become relatively mature. A variety of effective functional fillers have been developed to improve its load-bearing capacity, creep resistance and friction and wear performance. However, this type of functional filler is mainly inorganic fillers, and the content is often high when used in the field of wear-resistant lubrication, which inevitably causes a decrease in the tensile strength and flexibility of the composite material. Another defect of the existing composite modification technology is that it ignores the effect of friction heat on the friction and wear properties of polytetrafluoroethylene. Although polytetrafluoroethylene itself can withstand an ambient temperature as high as 220°C for a long time, under long-term friction shear, heat accumulation will inevitably occur on the surface of polytetrafluoroethylene friction parts, causing the softening and deformation of polytetrafluoroethylene, thereby reducing the lubrication performance and restricting the service life and reliability.
[0004] To this end, the present invention introduces creep-resistant, high-strength soluble polytetrafluoroethylene and polytetrafluoroethylene fibers into the polytetrafluoroethylene matrix, and improves the load-bearing capacity, friction and wear performance, and creep resistance of polytetrafluoroethylene through the modification and enhancement of homologous high molecular polymers. In particular, the higher specific surface area of polytetrafluoroethylene fibers is utilized to form a heat-conducting network through sizing with heat-conducting fillers, which promotes heat dissipation during friction. The inorganic lubricating filler in the composite system is controlled below 3% to ensure that the tensile strength and elongation at break of the composite material are at a high level. The developed polytetrafluoroethylene integral bearing does not require metal parts, has high load-bearing capacity, high thermal conductivity, high strength, high flexibility and excellent friction and wear performance, and especially has a higher PV value, and can be applied to transmission parts of mechanical devices in many industries such as chemical, automotive, pharmaceutical, and food. Summary of the invention
[0005] The purpose of the present invention is to provide a high PV value polytetrafluoroethylene integral sliding bearing and a preparation method thereof, so as to solve the problems in the existing bearing technology that polytetrafluoroethylene bearings need to be compounded with metal parts and are difficult to use independently, and the problems that the existing polytetrafluoroethylene composite modification technology has a high inorganic filler content, high brittleness, and unsatisfactory thermal conductivity.
[0006] 1. Preparation of polytetrafluoroethylene sliding bearings 1) Sizing modification: Add thermal conductive filler to polytetrafluoroethylene emulsion and disperse it evenly to prepare sizing solution; immerse polytetrafluoroethylene fiber in the sizing solution for 2 to 8 minutes, take it out, place it in an environment of 60 to 120°C and dry it for 15 to 100 minutes to remove the solvent; repeat sizing-drying 1 to 5 times.
[0007] 2) Mechanical blending: mechanically stirring the sized polytetrafluoroethylene fiber obtained in step 1) with the polytetrafluoroethylene resin, the soluble polytetrafluoroethylene resin and the lubricating filler at an ambient temperature of -35°C to -5°C until the mixture is uniformly mixed to obtain a mixture; 3) Hot pressing: the mixture obtained in step 2) is filled into a ring-shaped mold with an inner diameter of 10-50 mm, a cavity of 2-5 mm, and a height of 20-110 mm, and pre-pressed at a pressure of 25-60 MPa for 1-10 min; after demolding and removing the flash, the temperature is raised to 330-375° C. in a polytetrafluoroethylene sintering furnace and sintered for 30-120 min.
[0008] In step 1), the thermal conductive filler is one or more of aluminum nitride, graphene, nano-carbon fiber or boron nitride, with a thermal conductivity of 200-2000 W / (m·K) and a size of 30-300 nm; the mass concentration of polytetrafluoroethylene emulsion is 10%-50%, and the particle size of polytetrafluoroethylene in the emulsion is 30-200 nm; the diameter of polytetrafluoroethylene fiber is 50-200 μm, and the aspect ratio is 1-10. The amount of thermal conductive filler added is 0.5%-8% of the mass of polytetrafluoroethylene emulsion.
[0009] The mass percentages of the polytetrafluoroethylene resin, soluble polytetrafluoroethylene resin, sizing polytetrafluoroethylene fiber and lubricating filler in the mixture in step 2) are 35-50%, 30-45%, 2-35% and 1-3% respectively. The particle size of the polytetrafluoroethylene resin is 30-120 μm; the particle size of the soluble polytetrafluoroethylene resin is 30-150 μm, and the content of perfluorovinyl ether modified monomer is 0.02%-0.15%; the lubricating filler is one or more of graphite, aluminum bronze, graphite fluoride, molybdenum disulfide and boron nitride, and the particle size is 20-55 μm.
[0010] The present invention introduces soluble polytetrafluoroethylene to modify polytetrafluoroethylene and polytetrafluoroethylene fibers to construct a polymer alloy to improve the load-bearing capacity, friction and wear performance and creep resistance of the composite material; polytetrafluoroethylene fibers modified by thermal conductive filler sizing are used as the main reinforcing filler to improve the thermal conductivity and load-bearing capacity of the composite material while avoiding the decrease in strength and toughness caused by the introduction of a large amount of high modulus inorganic fillers; at the same time, with the help of a small amount of lubricating fillers, the friction coefficient and wear rate of the bearing are further reduced. In terms of manufacturing process, low-temperature blending is used to prevent polytetrafluoroethylene from agglomerating during mechanical stirring.
[0011] 2. Structural Characterization of PTFE Sliding Bearings The shape and microstructure of the polytetrafluoroethylene sliding bearing were observed using an optical microscope and a scanning electron microscope. The results are shown in the attached figure. Figure 1 and 2 shown.
[0012] Figure 1 The overall shape of the polytetrafluoroethylene sliding bearing. As can be seen from the figure, the surface of the prepared sliding bearing is smooth and flat, without obvious defects such as cracks, pores and bubbles.
[0013] Figure 2 This is the microscopic morphology of a polytetrafluoroethylene sliding bearing. As can be seen from the figure, after being sized with a polytetrafluoroethylene emulsion containing thermal conductive fillers, small-sized granular thermal conductive fillers are distributed on the surface of the polytetrafluoroethylene fiber; at the same time, the fiber is well combined with the polymer alloy matrix, and no obvious separation or cracks are observed.
[0014] 3. Performance of PTFE sliding bearings 1. Mechanical properties test The samples prepared in Examples 1 to 3 were punched and cut into dumbbell shapes of 80 mm×10 mm×4 mm, and the tensile strength and elongation at break were tested on a universal testing machine according to GB / T 1040.2-2022. The data are listed in Table 1.
[0015] 2. Thermal conductivity test The samples prepared in Examples 1 to 3 were machined into discs of φ12.7 mm×2 mm and tested on a thermal conductivity tester according to GJB / T1201.1-91. The data are listed in Table 1.
[0016] 3. PV value and friction coefficient test The samples prepared in Examples 1 to 3 were tested for PV value and friction coefficient under variable load and constant speed conditions according to GB / T 7948-1987. The test piece is a sleeve bearing with an inner diameter of 35 mm, an outer diameter of 41 mm, and a length of 35 mm. The test steel sleeve material is 45 steel with a surface hardness of 43 to 47 HRC. The linear speed during the test was 0.25 m / s, and the test was first run-in at 1 MPa for 30 minutes, and then increased by 1 MPa each time for 10 minutes. The bearing failure was determined until one of the following three situations occurred: Friction or temperature rise increases dramatically; The amount of wear reaches the limit value of the material being tested; The temperature rise reaches the limit value of the material being tested. At this time, the load ( P ) and line speed ( V The product of ) is the PV value. The friction coefficient is the average value of the friction coefficient in the whole test cycle. The data are listed in Table 1.
[0017] Table 1 Performance of polytetrafluoroethylene sliding bearings prepared in Examples 1 to 3 As shown in Table 1, the tensile strength of the polytetrafluoroethylene bearing prepared by the present invention is 20~32MPa, the elongation at break is 150%~280%, the thermal conductivity is (0.55~0.92)W / (m·K), the PV value is (2.0~3.8)MPa·m / s, and the friction coefficient is 0.02~0.04. It can be seen that under the component system described in the present invention, the polytetrafluoroethylene bearings prepared have higher tensile strength and elongation; in particular, the polytetrafluoroethylene fibers have a larger thermal conductivity, PV value and lower friction coefficient after being sized with thermal conductive fillers. In contrast, the polytetrafluoroethylene fibers used in the preparation of polytetrafluoroethylene bearings in Comparative Example 1 were not sized with thermal conductive fillers, and the PV value was only 1.75MPa·m / s, and when the load rose to 7MPa, the surface temperature suddenly increased, resulting in lubrication failure. In comparative example 2, when preparing polytetrafluoroethylene bearings, fusible polytetrafluoroethylene was not used to alloy the matrix, resulting in insufficient fluidity of the resin when it was melted, causing the thermal conductive filler and the lubricating filler to be isolated by PTFE, and the thermal conductivity coefficient was only 0.37 W / (m·K), and its PV value was only 1.30 MPa·m / s. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1The shape and morphology of the polytetrafluoroethylene bearings obtained in Examples 1 and 2 of the present invention.
[0019] Figure 2 The figure shows the internal microstructure of the polytetrafluoroethylene bearing of the present invention. DETAILED DESCRIPTION
[0020] The preparation and performance of the polytetrafluoroethylene bearing of the present invention are further described below through specific examples.
[0021] Example 1 (1) Sizing modification: 20 g of aluminum nitride (thermal conductivity 230 W / mK, size 300 nm) was added to 400 g of polytetrafluoroethylene emulsion (mass concentration 50%, particle size 60 nm) and dispersed evenly to prepare a sizing solution; 300 g of polytetrafluoroethylene chopped fibers (diameter 50 μm, aspect ratio 5) were immersed in the sizing solution for 2 min, then taken out and placed in a 60 °C environment for drying for 15-100 min to remove the solvent; the sizing-drying process was repeated once.
[0022] (2) Mechanical blending: 280 g of the sized polytetrafluoroethylene fiber obtained in step 1), 400 g of polytetrafluoroethylene resin (particle size 60 μm), 400 g of soluble polytetrafluoroethylene resin (particle size 30 μm, perfluorovinyl ether modified monomer content 0.025%) and 20 g of boron nitride (particle size 20 μm) were mechanically stirred at ambient temperature -15°C until they were uniformly mixed; (3) Hot pressing: 26.7 g of the mixture obtained in step 2) was filled into a ring-shaped mold with an inner diameter of 35 mm, a cavity of 3 mm, and a height of 35 mm, and pre-pressed at a pressure of 40 MPa for 5 min. After demolding and removing the flash, the temperature was raised to 365°C in a special sintering furnace for PTFE and sintered for 60 min to obtain a PTFE bearing with an inner diameter of 35 mm, an outer diameter of 41 mm, and a height of 35 mm. Its morphology is shown in the attached figure. Figure 1 The left side is white, and the properties are listed in Table 1.
[0023] Example 2 (1) Sizing modification: 40 g of graphene (thermal conductivity 1800 W / mK, size 50 nm) was added to 800 g of polytetrafluoroethylene emulsion (mass concentration 40%, particle size 50 nm) and dispersed evenly to prepare a sizing solution; 120 g of polytetrafluoroethylene chopped fibers (diameter 150 μm, aspect ratio 10) were immersed in the sizing solution for 7 min, then taken out and dried at 100 °C for 15 min to remove the solvent; the sizing-drying process was repeated 3 times.
[0024] (2) Mechanical blending: 58 g of the sized polytetrafluoroethylene fiber obtained in step 1), 70 g of polytetrafluoroethylene resin (particle size 30 μm), 70 g of soluble polytetrafluoroethylene resin (particle size 50 μm, perfluorovinyl ether modified monomer content 0.10%) and 2 g of graphite (particle size 50 μm) were mechanically stirred at ambient temperature -10°C until they were uniformly mixed; (3) Hot pressing: 28.9 g of the mixture obtained in step 2) was filled into a ring-shaped mold with an inner diameter of 35 mm, a cavity of 3 mm, and a height of 35 mm, and pre-pressed at a pressure of 45 MPa for 10 min. After demolding and removing the flash, the temperature was raised to 375°C in a special sintering furnace for PTFE and sintered for 100 min to obtain a PTFE bearing with an inner diameter of 35 mm, an outer diameter of 41 mm, and a height of 35 mm. Its morphology is shown in the attached figure. Figure 1 The right side is black, and the microscopic appearance is as shown in the attached Figure 2 The performance is listed in Table 1.
[0025] Example 3 (1) Sizing modification: 10 g of carbon nanofiber (thermal conductivity 1750 W / mK, size 50 nm) and 10 g of boron nitride (thermal conductivity 400 W / mK, size 180 nm) were added to 2000 g of polytetrafluoroethylene emulsion (mass concentration 10%, particle size 30 nm) and dispersed evenly to prepare a sizing solution; 80 g of polytetrafluoroethylene chopped fibers (diameter 120 μm, aspect ratio 1) were immersed in the sizing solution for 8 min, then taken out and dried at 120 °C for 100 min to remove the solvent; the sizing-drying process was repeated twice.
[0026] (2) Mechanical blending: 36 g of the sized polytetrafluoroethylene fiber obtained in step 1), 50 g of polytetrafluoroethylene resin (particle size 60 μm), 30 g of soluble polytetrafluoroethylene resin (particle size 150 μm, perfluorovinyl ether modified monomer content 0.05%) and 1 g of fluorinated graphite (particle size 55 μm) were mechanically stirred at ambient temperature -35°C until they were uniformly mixed; (3) Hot pressing: 26.0 g of the composite material obtained in step 2) was filled into a ring-shaped mold with an inner diameter of 35 mm, a cavity of 3 mm, and a height of 35 mm, and pre-pressed at a pressure of 30 MPa for 2 min. After demolding and removing the flash, the temperature was raised to 345°C in a special polytetrafluoroethylene sintering furnace and sintered for 45 min to obtain a polytetrafluoroethylene bearing with an inner diameter of 35 mm, an outer diameter of 41 mm, and a height of 35 mm. Its properties are listed in Table 1.
[0027] Comparative Example 1 (1) Mechanical blending: 56 g of polytetrafluoroethylene fiber (diameter 150 μm, aspect ratio 10), 2 g of graphene (thermal conductivity 1800 W / mK, size 50 nm), 70 g of polytetrafluoroethylene resin (particle size 30 μm), 70 g of soluble polytetrafluoroethylene resin (particle size 50 μm, perfluorovinyl ether modified monomer content 0.10%) and 2 g of graphite (particle size 50 μm) were mechanically stirred at ambient temperature -10 °C until the mixture was uniformly mixed; (2) Hot pressing: 28.9 g of the composite material obtained in step 2) was filled into a ring-shaped mold with an inner diameter of 35 mm, a cavity of 3 mm, and a height of 35 mm, and pre-pressed at a pressure of 45 MPa for 10 min. After demolding and removing the flash, the temperature was raised to 375°C in a special polytetrafluoroethylene sintering furnace and sintered for 100 min to obtain a polytetrafluoroethylene bearing with an inner diameter of 35 mm, an outer diameter of 41 mm, and a height of 35 mm. The properties are listed in Table 1.
[0028] Comparative Example 2 (1) Sizing modification: 10 g of carbon nanofiber (thermal conductivity 1750 W / mK, size 50 nm) and 10 g of boron nitride (thermal conductivity 400 W / mK, size 180 nm) were added to 2000 g of polytetrafluoroethylene emulsion (mass concentration 10%, particle size 30 nm) and dispersed evenly to prepare a sizing solution; 80 g of polytetrafluoroethylene chopped fibers (diameter 120 μm, aspect ratio 1) were immersed in the sizing solution for 8 min, then taken out and dried at 120 °C for 100 min to remove the solvent; the sizing-drying process was repeated twice.
[0029] (2) Mechanical blending: 36 g of the sized polytetrafluoroethylene fiber obtained in step 1), 80 g of polytetrafluoroethylene resin (particle size 60 μm) and 1 g of fluorinated graphite (particle size 55 μm) were mechanically stirred at ambient temperature -35°C until the mixture was uniformly mixed; (3) Hot pressing: 26.0 g of the composite material obtained in step 2) was filled into a ring-shaped mold with an inner diameter of 35 mm, a cavity of 3 mm, and a height of 35 mm, and pre-pressed at a pressure of 30 MPa for 2 min. After demolding and removing the flash, the temperature was raised to 345°C in a special polytetrafluoroethylene sintering furnace and sintered for 45 min to obtain a polytetrafluoroethylene bearing with an inner diameter of 35 mm, an outer diameter of 41 mm, and a height of 35 mm. Its properties are listed in Table 1.
Claims
1. A method for preparing a high PV value polytetrafluoroethylene integral sliding bearing, characterized in that: The following steps are involved: 1) Sizing modification: Add the thermal conductive filler to the polytetrafluoroethylene emulsion and disperse it evenly to prepare the sizing solution; The polytetrafluoroethylene fiber is immersed in the sizing solution for 2 to 8 minutes, then taken out and placed in a 60 to 120°C environment for drying for 15 to 100 minutes to remove the solvent; the sizing-drying is repeated 1 to 5 times; 2) Mechanical blending: mechanically stirring the sized polytetrafluoroethylene fiber obtained in step 1) with the polytetrafluoroethylene resin, the soluble polytetrafluoroethylene resin and the lubricating filler at an ambient temperature of -35°C to -5°C until the mixture is uniformly mixed to obtain a mixture; 3) Hot pressing: the mixture obtained in step 2) is filled into a ring-shaped mold with an inner diameter of 10-50 mm, a cavity of 2-5 mm, and a height of 20-110 mm, and pre-pressed at a pressure of 25-60 MPa for 1-10 min; after demolding and removing the flash, the temperature is raised to 330-375° C. in a polytetrafluoroethylene sintering furnace and sintered for 30-120 min.
2. The method for preparing a high PV value polytetrafluoroethylene integral sliding bearing as claimed in claim 1, characterized in that: In step 1), the thermal conductive filler is one or more of aluminum nitride, graphene, nano-carbon fiber or boron nitride, with a thermal conductivity of 200-2000 W / (m·K) and a size of 30-300 nm; the mass concentration of the polytetrafluoroethylene emulsion is 10%-50%, and the particle size of the polytetrafluoroethylene in the emulsion is 30-200 nm; the diameter of the polytetrafluoroethylene fiber is 50-200 μm, and the aspect ratio is 1-10.
3. The method for preparing a high PV value polytetrafluoroethylene integral sliding bearing as claimed in claim 1, characterized in that: In step 1), the amount of the thermally conductive filler added is 0.5% to 8% of the mass of the polytetrafluoroethylene emulsion.
4. The method for preparing a high PV value polytetrafluoroethylene integral sliding bearing as claimed in claim 1, characterized in that: The mass percentages of the polytetrafluoroethylene resin, the soluble polytetrafluoroethylene resin, the sizing polytetrafluoroethylene fiber and the lubricating filler in the mixture in step 2) are 35-50%, 30-45%, 2-35% and 1-3% respectively.
5. The method for preparing a high PV value polytetrafluoroethylene integral sliding bearing as claimed in claim 1, characterized in that: In step 2), the particle size of the polytetrafluoroethylene resin is 30-120 μm; the particle size of the soluble polytetrafluoroethylene resin is 30-150 μm, and the content of the perfluorovinyl ether modified monomer is 0.02%-0.15%; the lubricating filler is one or more of graphite, aluminum bronze, graphite fluoride, molybdenum disulfide, and boron nitride, and the particle size is 20-55 μm.
6. A high PV value polytetrafluoroethylene integral sliding bearing prepared by the method of claim 1.
Citation Information
Patent Citations
Composite material of high-temperature resistant metal-fabric / resin self-lubricating bearing and preparation method of composite material
CN102145556A
Polytetrafluoroethylene sealing material used for high-speed high-pressure hydraulic oil cylinder as well as preparation method and application of sealing material
CN108102262A
Bearing lubricating material based on modified polytetrafluoroethylene and modified carbon fibers
CN117070040A
Polytetrafluoroethylene bearing material based on interface modification
CN118307908A
Implantable material and method of preparing same
US4118532A
Cited By
Polytetrafluoroethylene composition, polytetrafluoroethylene composite material, preparation method of polytetrafluoroethylene composite material and sealing material
CN120682586A
Low-creep polytetrafluoroethylene composite material and preparation method thereof
CN120923949A